2020
DOI: 10.3390/ph13060113
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Seeking Matrix Metalloproteinase Inhibitors for the Treatment of Skeletal Malignancy

Abstract: Matrix metalloproteinases (MMPs) are a family of enzymes involved at different stages of cancer progression and metastasis. We previously identified a novel class of bisphosphonic inhibitors, selective for MMPs crucial for bone remodeling, such as MMP-2. Due to the increasing relevance of specific MMPs at various stages of tumor malignancy, we focused on improving potency towards certain isoforms. Here, we tackled MMP-9 because of its confirmed role in tumor invasion, metastasis, angiogenesis, and immuno-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For this reason, moreover, the binding mode obtained for these ligands in all MMPs is not well conserved; one phosphonic group coordinates the zinc ion following the crystallographic tetrahedral geometry, while the other can line up to the binding mode observed in the X-ray complex [ 18 ] for some ligands. At the same time, for other ligands, the second phosphonic group reaches Leu164 and Ala165 NHs, providing key H-bonds and allowing the aromatic group to reach deeper in the S1′ site, as observed for arylamino-derivatives that possess the same structural frame [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, moreover, the binding mode obtained for these ligands in all MMPs is not well conserved; one phosphonic group coordinates the zinc ion following the crystallographic tetrahedral geometry, while the other can line up to the binding mode observed in the X-ray complex [ 18 ] for some ligands. At the same time, for other ligands, the second phosphonic group reaches Leu164 and Ala165 NHs, providing key H-bonds and allowing the aromatic group to reach deeper in the S1′ site, as observed for arylamino-derivatives that possess the same structural frame [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lead compound ML115 showed high potency and was also endowed with antiosteoclastic activity, which could reduce skeletal disease burden in patients with conditions involving abnormal bone resorption [ 8 , 17 ]. Further developments along this line of research showed that modifications on the arylbisphosphonic scaffold could afford compounds which selectively inhibit MMP-2 [ 8 , 15 , 17 ] and MMP-9 [ 18 ], and that also exhibit significant potential for bone malignancy therapy, being superior at promoting cancer apoptosis than standard-of-care bisphosphonates, such as zoledronic acid [ 8 , 17 ]. Moreover, these bisphosphonic MMPIs (BMMPIs) showed no particular side effects in vivo at therapeutic dosages [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laghezza and his colleagues have designed a bisphosphonic acid inhibitor, ML 115. [ 16 ] This substance is based on sulfonamide, which is treated with diethyl phosphite to obtain a series of aromatic bisphosphonic acid derivatives. These bisphosphonic acid derivatives target tumor cells by interacting with the side chains of MMPs at specific sites due to the different bonding mechanisms of the two phosphine groups.…”
Section: Materials and Methods: Nanomaterials Applied To Tme Response...mentioning
confidence: 99%